2009
DOI: 10.1126/science.1165884
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Active Sites Cause Size-Selective Reactivity of Aluminum Cluster Anions with Water

Abstract: The reactions of metal clusters with small molecules often depend on cluster size. The selectivity of oxygen reactions with aluminum cluster anions can be well described within an electronic shell model; however, not all reactions are subject to the same fundamental constraints. We observed the size selectivity of aluminum cluster anion reactions with water, which can be attributed to the dissociative chemisorption of water at specific surface sites. The reactivity depends on geometric rather than electronic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
288
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 272 publications
(315 citation statements)
references
References 22 publications
24
288
3
Order By: Relevance
“…Clusters of this kind composed of tungsten and oxygen are reported for the first time in the gas phase. The presence of prominent peaks for W 6 -, especially for these compositions is supported by the computed atomization energies of these clusters which reveal enhanced stabilities for these compositions. Structure and stability of these unique magic numbered clusters will be of great interest, especially for their catalytic applications.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Clusters of this kind composed of tungsten and oxygen are reported for the first time in the gas phase. The presence of prominent peaks for W 6 -, especially for these compositions is supported by the computed atomization energies of these clusters which reveal enhanced stabilities for these compositions. Structure and stability of these unique magic numbered clusters will be of great interest, especially for their catalytic applications.…”
Section: Resultsmentioning
confidence: 63%
“…Closed-cage clusters of composition, W 6 -were detected in the laser desorption mass spectra of W-Se and W-S mixtures. Further study of the precursor revealed the formation of nano tungsten oxide from a mixture of W and Se.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Conventional ab initio molecular dynamics simulation has revealed rapid hydrogen production from water by a cluster (or superatom) consisting of a magic number of aluminum atoms, Al 17 . We found a low activation-barrier mechanism, in which a pair of Lewis acid and base sites on the Al n surface preferentially catalyzes hydrogen production.…”
Section: Discussionmentioning
confidence: 99%
“…This is followed by a chain of hydrogen bond switching events (denoted by arrows in figure 9(a)) that involves in total of four H 2 O molecules, and finally a hydrogen atom bonds to an Al atom after 190 fs. This proton transfer is induced by the Lewis acidbase characters of the participating Al atoms [17]. Although it is hard for the water molecule to dissociate by itself, the Grotthuss mechanism greatly reduces the activation barrier for the dissociation.…”
Section: Low Activation-barrier Mechanism Of Hydrogen Productionmentioning
confidence: 99%